2018
DOI: 10.1021/acsami.8b02509
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Octagon-to-Square Wetting Interface Transition of Evaporating Sessile Droplet through Surfactant on Microtextured Surface

Abstract: Producing and maintaining specific liquid patterns during evaporation holds great potential for techniques of printing and coating. Here we report the control over the evolution of surfactant solution droplets on the micropyramid substrates during evaporation. The polygonal droplet shape is achieved during the drying rather than solely at the beginning. As the initial surfactant concentration is 0.04 mM, the droplet maintains its initial octagonal shape throughout the lifetime. Interestingly, the initial octag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Liquids in the Wenzel wetting state present a completely wetting solid-liquid contact area, desirable features for pesticide retention on plant surfaces 17 and boiling heat transfer 18 . Using highly enhanced capillarity and contact line pinning, spectacular properties of the Wenzel wetting state have been discovered, including directional and multilayer liquid spreading, as well as the formation of polygonal thin-liquid films and droplets 19 28 . For instance, Courbin et al 20 , 21 investigated deposited liquids on microtextured surfaces satisfying the imbibition condition and showed that they can form square, hexagonal, octagonal, and circular-shaped thin-liquid films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquids in the Wenzel wetting state present a completely wetting solid-liquid contact area, desirable features for pesticide retention on plant surfaces 17 and boiling heat transfer 18 . Using highly enhanced capillarity and contact line pinning, spectacular properties of the Wenzel wetting state have been discovered, including directional and multilayer liquid spreading, as well as the formation of polygonal thin-liquid films and droplets 19 28 . For instance, Courbin et al 20 , 21 investigated deposited liquids on microtextured surfaces satisfying the imbibition condition and showed that they can form square, hexagonal, octagonal, and circular-shaped thin-liquid films.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges lie in several aspects. First, liquid fronts can proceed spontaneously for complete and partial wetting cases 19 28 . However, thermodynamics suggests that capillary imbibition cannot take place on non-wetting surfaces 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Very recent work (Zhong et al [16]) involved the addition of surfactants to control wetting geometry.…”
Section: ~√mentioning
confidence: 99%
“…Interestingly, compared with the study of ethanol droplets done by Feng et al, both KCl and ethanol produced the same effect on the shape of droplets, despite the different effect that these solutions have on surface tension. The study of droplet profile as a function of surfactant concentration on textured surfaces showed different wetting transitions of evaporating droplets, corresponding to the initial surfactant concentration [31,32] . The transition of droplet profile from octagon to square, and from square to rectangle, was observed during the drying process.…”
Section: Introductionmentioning
confidence: 99%
“…The transition of droplet profile from octagon to square, and from square to rectangle, was observed during the drying process. Additionally, the ability to maintain a uniform droplet profile throughout the whole evaporation process was achieved for octagonal droplets [31,32] . The findings unanimously demonstrate that surface chemistry and topography, as well as the intrinsic contact angle of the fluid, govern the wetting dynamics and droplet shape.…”
Section: Introductionmentioning
confidence: 99%